Validation of Computational Fluid Dynamics (CFD) Model of a Building Integrated Photovoltaic/Thermal (BIPV/T) System. (November 2015) - Roeleveld, D.; Hailu, G.; Fung, A.S.; Naylor, D.; Yang, T.; Athienitis, A.K.
Abstract: A building integrated photovoltaic/thermal (BIPV/T) system was studied using computational fluid dynamics (CFD). The BIPV/T system was composed of solar photovoltaic (PV) panels mounted in front of a wall/roof with an air channel in between. A numerical model was developed consisting of a PV layer, an air channel, and an insulation and plywood layer. Experiments were conducted by the Solar Simulator Laboratory at Concordia University using three different orientations of 0°, 45° and 90° at two different flow rates. A comparison of the temperatures profiles between the numerical predictions and the experimental data is presented. Overall, the numerical results were in good agreement with the experimental data.